SELF-EFFICACY DALAM PEMBELAJARAN MATEMATIKA SISWA MADRASAH ALIYAH - Maria Ulpah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
Self-efficacy of students plays a role in determining student success in learning, including learning mathematics. Affective aspects such as self-efficacy, play a major role when students work and use mathematics, because to be able to solve mathematical problems is not enough just to know how to do it, but must be accompanied by self-efficacy about the truth of the concepts and procedures they have. This research was conducted in two groups of students using an instrument in the form of a questionnaire to measure students' self-efficacy. Observation data collection techniques were also conducted to determine the learning process of the two groups. The results showed that groups of students who used active and cooperative learning had higher self-efficacy. Keywords: self-efficacy, mathematics, cooperative learning.